2021
DOI: 10.21315/eimj2021.13.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening: Knowledge and Practice among Private General Practitioners in Northeast Peninsular Malaysia

Abstract: Colorectal cancer screening is an important screening to detect colorectal cancer. Thus, the aim of this study is to determine the knowledge, practice and its associated factors of colorectal cancer screening among private general practitioners (PGPs) in Northeast Peninsular Malaysia. Crosssectional study was conducted involving 127 PGPs in Kelantan. The study used a validated selfadministrated questionnaire that contained three domains. The domains were sociodemographic, knowledge and practice of colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, our study results showed a better knowledge about CRC screening among primary care physicians compared to a study done in Saudi Arabia that showed only about 34% of their primary care physicians had good knowledge about CRC screening and around 21% of primary care physicians had good knowledge about CRC screening in a similar study done in Malaysia. 19,21 In this study, most primary care physicians (63.2%) were able to identify the appropriate age of initiating CRC screening and 69% correctly answered that fecal occult blood testing should be repeated annually as a screening method for CRC screening. However only 49.4% correctly answered that colonoscopy should be repeated every 10 years for CRC screening.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Furthermore, our study results showed a better knowledge about CRC screening among primary care physicians compared to a study done in Saudi Arabia that showed only about 34% of their primary care physicians had good knowledge about CRC screening and around 21% of primary care physicians had good knowledge about CRC screening in a similar study done in Malaysia. 19,21 In this study, most primary care physicians (63.2%) were able to identify the appropriate age of initiating CRC screening and 69% correctly answered that fecal occult blood testing should be repeated annually as a screening method for CRC screening. However only 49.4% correctly answered that colonoscopy should be repeated every 10 years for CRC screening.…”
Section: Resultsmentioning
confidence: 81%
“…The result of this study is consistent with other studies that relieved low level of practice among primary care physicians. 19,24,26 Most of the participants (89.7%) in this study reported lack of time as one of the barriers that hinder them from screening their patients for CRC. The regular consultation visit time is eight minutes, hence physicians might not get adequate time to explain to patients about performing FOBT to screen for CRC.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations